Targeted anti-colon cancer activities of a millet bran-derived peroxidase were mediated by elevated ROS generation. Issue 7 (8th July 2015) - Shan, Shuhua; Shi, Jiangying; Li, Zhen; Gao, Huixian; Shi, Tonglin; Li, Zongwei; Li, Zhuoyu
<x xml:space="preserve">Abstract</x> Foxtail millet (Setaria italica) is the sixth most important cereal in the world.